Modeling whole farm profitability and environmental performance of four alfalfa‐grass binary mixtures in eastern Canadian dairy farms. (28th August 2021) - Ouellet, Veronique; Tremblay, Gaëtan F.; Laroche, Jean‐Philippe; Bélanger, Gilles; Binggeli, Simon; Jégo, Guillaume; Charbonneau, Edith
Abstract: Forages are a major source of nutrients for milk production, but little is known about the effects of forage species on whole‐farm profitability and environmental performance. Using a whole‐farm approach, the N‐CyCLES (Nutrient‐Cycling Crops‐Livestock‐Environment‐Soil) optimization model, and experimentally measured data, this study aimed to compare the profitability and environmental performance of dairy farms when four alfalfa ( Medicago sativa L.)‐grass binary mixtures harvested and stored as silage and hay are used in ration formulation of heifers and lactating and dry cows: (a) alfalfa‐timothy ( Phleum pratense L.) (Al+Tim), (b) alfalfa‐tall fescue [ Schedonorus arundinaceus (Schreb.) Dumort.] (Al+TF), (c) alfalfa‐meadow fescue fescue [ Schedonorus pratensis (Huds.) P. Beauv.] (Al+MF), and (d) alfalfa‐meadow bromegrass ( Bromus biebersteinii Roem. & Schult.) (Al+Bro). Simulations were conducted on two virtual eastern Canadian dairy farms: southwestern (SWQ) and eastern Quebec (EQ). Comparisons were based on net income, greenhouse gas emissions, and nutrient balances. In SWQ, Al+Bro and Al+Tim led to the highest net income, but only slight differences were calculated between the four mixtures (maximum difference of 1.4%). In EQ, results suggested that Al+TF is the most viable alternative to Al+Tim mixtures as it allowed the farm to reach the highest profit (maximum difference of 8%). The choice of grass in alfalfa‐grass binary mixture had little impact on the farm's total greenhouse gas emissions: the lowest total greenhouse gas emissions were with Al+ MF in SWQ and with Al+TF in EQ. In SWQ, phosphorus balance was low for the four mixtures and the lowest nitrogen balance was reached with Al+MF and Al+Tim. Finally, in EQ, the lowest phosphorus balance was reached with Al+MF, whereas the lowest nitrogen balance was reached with Al+Bro. In conclusion, despite slight differences, all grass species tested allowed the farm to reach similar profits and environmental performance. Core Ideas: Forages grown on‐farm should be regionally and farm‐characteristic oriented. Comparable net incomes were obtained with all binary mixtures tested within a region. The choice of mixture grown on‐farm had little impact on environmental performance. No alfalfa‐grass mixture maximized profits while minimizing environmental footprint.